Life-span human development - Anderson, Ariel L. H. (Harcourt Brace Jovanovich, 1991)
Known for its clear, straightforward writing style, comprehensive coverage, strong and current research-based approach, and excellent visuals and tables, LIFE-SPAN HUMAN DEVELOPMENT offers sections on four life stages: infancy, childhood, adolescence, and adulthood. Each chapter focuses on a domain of development such as physical growth, cognition, or personality, and traces developmental trends and influences in that domain from infancy to old age. This unique, topical organization helps you comprehend the processes of transformation occurring in each key area of human development. The new edition includes a clear focus on the complex interactions of nature and nurture in development, more integrated coverage of culture and diversity, and an exciting new media package for students